2021
DOI: 10.1016/j.cub.2020.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Strategies for Learning in Males and Females

Abstract: Highlights d Sex influences the strategies used during reinforcement learning and decision making d Female mice used a consistent strategy that permitted faster acquisition d Male mice were more likely to change their strategy in response to prior reward d Differences in strategy are an underrecognized influence on reward-guided behavior

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 77 publications
3
54
2
Order By: Relevance
“…However, this is inconsistent with published research and there is evidence for sex differences in strategy in probabilistic bandits (Chen et al, 2021). It is possible that these results do not generalize to both sexes.…”
Section: Discussioncontrasting
confidence: 85%
“…However, this is inconsistent with published research and there is evidence for sex differences in strategy in probabilistic bandits (Chen et al, 2021). It is possible that these results do not generalize to both sexes.…”
Section: Discussioncontrasting
confidence: 85%
“…Our previous study suggested that males and females could achieve similar learning performance via divergent decision making strategies (Chen et al, 2020). However, different strategies might take different amounts of time to execute (Chen et al, 2020;Filipowicz et al, 2019;Kool et al, 2010;Kurdi et al, 2019). Therefore, if males and females had adopted strategies here, then we might expect response time to systematically differ between males and females, despite the similarities in learning performance.…”
Section: Resultsmentioning
confidence: 90%
“…Similar levels of accuracy do not require or imply a similar approach to the task. Our previous study suggested that males and females could achieve similar learning performance via divergent decision making strategies (Chen et al, 2020). However, different strategies might take different amounts of time to execute (Chen et al, 2020;Filipowicz et al, 2019;Kool et al, 2010;Kurdi et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations